Translation of Foreign Culturally Colourful Metaphors Into the Native Language - Mammadova, Samira J (e-Journal of Linguistics; Vol 14 No 2 (2020): e-jl JulyDO - 10.24843/e-jl.2020.v14.i02.p001, 2020)
Translation of culturally coloured words has long been in the focus of linguists. This lexicon is also called by linguists as the words without lexical equivalents in other languages. The question is actual for its importance for translators, who face with frequent difficulties in the process of translation of the texts with culturally coloured lexicon. Interpretation of culturally coloured metaphors requires not only a close acquaintance with the English culturally coloured words but also a sufficient information about the phraseological system of the native language. The semantical equivalents of English metaphors can be found in the native metaphorical system no matter in which lexical structures the identical or similar metaphorical meanings may find their expression. Possibility of finding the semantical equivalents of English metaphors in the native language is conditioned with the common thinking way of peoples speaking different languages who in their long life experience have come across with the same situations allowing to create similar metaphorical expressions in different lexical ways. Study of language and culture in close ties was always in the focus of linguists from the point of view of communication and translation from one language into another. Scientists come to the conclusion that any language has a special semantic field which creates a difficulty for translating from one language into another. Such a lexical layer reflects just the national background, ethic and aesthetic life of a concrete people formed during many years.